(untitled) (Fiep Bulletin - online, 2011)
This study aimed to lift the symptoms of pain in construction workers. The sample is composed of sixty (60) in the building industry, with a mean age of 46 years and standard deviation of ages equal to 3.68. The instrument used to assess symptoms of pain was the diagram Corlett. In results, the highest value was found for a bricklayer with 72.73% of the symptoms of pain and the lowest value was for a servant with 20.91%, indicating a percentage range of 51.82%. The results of the symptoms of pain, the sub-sample of masons and bricklayers had the same value of 46.2 and the lowest value obtained by letters. The highest value obtained was the sub-group of electricians, equal to 53.3, characterizing the group with more symptoms of pain.